Anti Odour Shoes / Nur Haniah Ab Malik - Ab Malik, Nur Haniah (2020)
HM Kickers Sdn Bhd is establising a new type of shoes that might be solving a specific group of consumer problem concerning their footwear. Our shoes exist because since the ancient time the problem of smelly feet due to sweat has caused many people to feel less confident in themselves just because of the smell of their feet. Therefore, like our company's slogan of "Be Confident" we want to help those who face the problem to appear more confident and increase their potential in themselves. Our target market is divided into three categories which is mass market, people who need to wear shoes for extended hours and sports athelets who live in urban area. Firstly, mass market. Our company main target market is mass market because we are targeting every level of society that face the problems of smelly feet. Next, we are targeting people who need to wear shoes for extended hours such as factory workers, army, hotel workers and others. This is because they are the group that needs to work in hot and humid conditions and they are also the group that is actively moving so the rate of sweat production in their body is very fast and causes their feet to smell quickly. Our last target market is sports atheletes. This is because sports athletes need to follow their strict and volatile training schedule. Sometimes they do not get enough rest and this has disrupted their body system and hormones. When their body system and hormones are disturbed it can cause various diseases and health problems to them and one of them is the problem of smelly feet caused by the uncontrolled rate of sweat production. These shoes are specially designed for those who have foot odor problems while providing precise comfort to users when wearing them because the technology we use is very sophisticated. The prices of our products are also very reasonable and affordable. Currently, there is no other company that make shoes with the same function as our company. Our company target production for second year is RM350 000.00. The management team of our company is divided into several section and each section is lead by experience and profesional employee in order to ensure our company’s quality and efficiency.